2009
DOI: 10.1016/j.susc.2009.04.016
|View full text |Cite
|
Sign up to set email alerts
|

The small unit cell reconstructions of SrTiO3(111)

Abstract: We analyze the basic structural units of simple reconstructions of the (111) surface of SrTiO 3 using density functional calculations. The prime focus is to answer three questions: what is the most appropriate functional to use; how accurate are the energies; what are the dominant low-energy structures and where do they lie on the surface phase diagram. Using test calculations of representative small molecules we compare conventional GGA with higher-order methods such as the TPSS meta-GGA and on-site hybrid me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…DFT calculations were carried out using the Wien2k code 16 , with, for improved accuracy, PBE0 and TPSSh on-site functionals as described elsewhere, with errors estimated from the differences between the functionals 20 . An RKmax parameter of 6.12 was used with RMTs of 2.36, 1.72 and 1.54 for strontium, titanium and oxygen, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DFT calculations were carried out using the Wien2k code 16 , with, for improved accuracy, PBE0 and TPSSh on-site functionals as described elsewhere, with errors estimated from the differences between the functionals 20 . An RKmax parameter of 6.12 was used with RMTs of 2.36, 1.72 and 1.54 for strontium, titanium and oxygen, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The horizontal axis is the composition in terms of excess monolayers of TiO 2 at the surface; negative numbers indicate an excess of SrO. Error bars were estimated on the basis of the differences in energies using various functionals 20 .…”
mentioning
confidence: 99%
“…While the approximate chemistry and topography of the surfaces is relatively well characterized as are some details of the dependence upon surface composition [21], the actual atomic structure of all these surfaces is completely unknown. A few theoretical studies in the literature focus on relatively simple structures that have not been found experimentally [22][23][24].…”
mentioning
confidence: 99%
“…Atomic positions were optimized using the full-electron potential WIEN2k package [28] with an augmented plane wave + local orbitals (APW+lo) basis set, the PBEsol [29] generalized gradient approximation as well as the revTPSS method [30]. Similar to work for the NiO (111) surface [31], we optimized the exact-exchange parameter for the Ti-d levels using experimental energies of some TiO x molecules [32] which gave a result of 0.5. While this is not a panacea of all DFT ills, and the exactexchange fraction is surprisingly large, this gave a noticeably better value of 1.36eV for the decomposition energy of SrTiO 3 to SrO and TiO 2 compared to previous work [32], a better band-gap of ~2.8(1) eV as well as a good absolute fit to the ratio of the surface free-energy of SrTiO 3 (001) to (110) from Wulff construction measurements [33], none of these being part of the fitting.…”
mentioning
confidence: 99%
“…Similar to work for the NiO (111) surface [31], we optimized the exact-exchange parameter for the Ti-d levels using experimental energies of some TiO x molecules [32] which gave a result of 0.5. While this is not a panacea of all DFT ills, and the exactexchange fraction is surprisingly large, this gave a noticeably better value of 1.36eV for the decomposition energy of SrTiO 3 to SrO and TiO 2 compared to previous work [32], a better band-gap of ~2.8(1) eV as well as a good absolute fit to the ratio of the surface free-energy of SrTiO 3 (001) to (110) from Wulff construction measurements [33], none of these being part of the fitting. Typical muffin-tin radii were 1.55, 1.75, and 2.36 Bohr for O, Ti, and Sr, respectively, a 1x1x1 k-point grid, and a plane wave cut-off of K max *min(RMT)=7.0.…”
mentioning
confidence: 99%